Oral candidiasis as a clinical marker related - J. Campo (Blackwell Synergy)
High viral load is currently considered to be one of the main indicators of the progression of HIV-induced immunodepression, but few studies have analysed its relationship to the presence of oral candidiasis (OC). The aim of this crosssectional study is to analyse the relationship between viral load, total CD4 lymphocyte count, and percentage of CD4 lymphocytes to the occurrence of OC.